Human enterprises, the new normality - Naranjo Picones, Carla Elisa (Scientific journal of social studies, 2023)
The pandemic has driven a radical shift in work practices, prompting companies to become more human and adapt to the “new normal.” Remote work has facilitated global hiring and brought forth technological and socio-emotional challenges for employees. Companies must support their staff and embrace collaborative structures, leaving behind hierarchical ones. These changes raise questions about the future of businesses and teamwork, while also offering opportunities for growth and mutual care. Evident solidarity and collaboration have strengthened work relationships. In conclusion, companies had to undergo significant changes due to the pandemic. There may be differing opinions among authors, but adopting measures that support employees’ mental health and goal fulfillment undeniably made them more humane.